Reinforcement learning from demonstration for robust control of superconducting qubits: Decoherence suppression via environmental engineering - Hamrouni, Chafaa; Abdelgader, Leila (Advances in Differential Equations and Control Processes, 2026)
This work develops a control-oriented theoretical framework for the manipulation of transient emission spectra and field-state purity in a qubit interacting with a broadband squeezed reservoir. We model the joint qubit-field dynamics using a time-resolved open quantum system formalism. This establishes a direct, quantitative connection between transient spectral characteristics, quantum purity evolution, and controllable system parameters. The analysis reveals that nonclassical reservoir properties, particularly squeezing-induced correlations, strongly influence both spectral deformation and coherence redistribution during the early-time dynamics. Building on this foundation, the work explores practical control strategies aimed at engineering the system’s dynamical response. Pulse shaping and time-dependent modulation of qubit-reservoir coupling offer effective control tools. These regulate spectral broadening, suppress unwanted decoherence, and accelerate convergence toward stabilized operating regimes. In addition, feedback-assisted qubit probing protocols are investigated as a means of monitoring and controlling field purity while minimizing measurement back-action on the squeezed mode. Our results show that well-designed control loops can balance information extraction and disturbance. This enables efficient regulation of nonclassical field properties. The proposed approach highlights transient spectral measurements as a powerful diagnostic and control resource, linking observable emission features to underlying quantum correlations and purity dynamics. From an engineering perspective, the framework offers practical guidelines. These guide the design of feedback-stabilized quantum emitters and reservoir-engineered coherence control. These findings are directly relevant to emerging quantum technologies, including cavity and circuit quantum electrodynamics, quantum sensing, and quantum communication systems operating in nonclassical environments.